Surplus Carbon Drives Allocation and Plant–Soil Interactions. (December 2020) - Prescott, Cindy E.; Grayston, Sue J.; Helmisaari, Heljä-Sisko; Kaštovská, Eva; Körner, Christian; Lambers, Hans; Meier, Ina C.; Millard, Peter; Ostonen, Ivika
Abstract : Plant growth is usually constrained by the availability of nutrients, water, or temperature, rather than photosynthetic carbon (C) fixation. Under these conditions leaf growth is curtailed more than C fixation, and the surplus photosynthates are exported from the leaf. In plants limited by nitrogen (N) or phosphorus (P), photosynthates are converted into sugars and secondary metabolites. Some surplus C is translocated to roots and released as root exudates or transferred to root-associated microorganisms. Surplus C is also produced under low moisture availability, low temperature, and high atmospheric CO2 concentrations, with similar below-ground effects. Many interactions among above- and below-ground ecosystem components can be parsimoniously explained by the production, distribution, and release of surplus C under conditions that limit plant growth. Highlights: Plant growth is normally constrained by nutrients, water or temperature, not photosynthesis, and plants often have surplus carbohydrates. Secondary metabolites are produced in N-limited plants primarily to dispose of surplus carbon, although they may subsequently help reduce browsing damage. Surplus carbohydrates are translocated from leaves and below ground some are discharged via exudates and mycorrhizal fungi. Root exudates contain more of the elements that plants have in surplus, and less of those in short supply. The abundance and type of mycorrhizal fungi is influenced by the amount and composition of surplus carbon in roots. Surplus carbon provides an alternative lens though which to view interactions between plants and soil organisms.